2013
DOI: 10.1002/chem.201300374
|View full text |Cite
|
Sign up to set email alerts
|

Diazido Mixed‐Amine Platinum(IV) Anticancer Complexes Activatable by Visible‐Light Form Novel DNA Adducts

Abstract: Platinum diam(m)ine complexes, such as cisplatin, are successful anticancer drugs, but suffer from problems of resistance and side-effects. Photoactivatable PtIV prodrugs offer the potential of targeted drug release and new mechanisms of action. We report the synthesis, X-ray crystallographic and spectroscopic properties of photoactivatable diazido complexes trans,trans,trans-[Pt(N3)2(OH)2(MA)(Py)] (1; MA=methylamine, Py=pyridine) and trans,trans,trans-[Pt(N3)2(OH)2(MA)(Tz)] (2; Tz=thiazole), and interpret the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 58 publications
2
81
2
1
Order By: Relevance
“…As imilar topic was also explored by Vicha et al [22] In contrastt op revious authors, they used the relativistic approach, that is, the two-component zeroth-order regular approximation (SO-ZORA) with the PBE0/TZP/COSMO computational level for successful determination of the NMR shielding constants.A nother interesting paper was recently published by Wilson et al [23] where, by combining experimental and computational tools, the oxidation of platinum(II) complexesw ith iodobenzene dichloride in DMF was studied, yieldingt he respectivep latinum(IV) analogues.T ime-dependent (TD)-DFT/ LANL2DZ/COSMO approachw as employed for the determination of the singlet excited states of both sets of Pt II and Pt IV complexes.T he calculations confirmed that the quenching of an excitation state (originally based on the LUMO in the Pt II complex) arises from the presence of metal-based dorbitals energetically positioned between the HOMO and the LUMO of the fluorophore ligand. Similar supporting calculations on diazido-platinum(IV) complexes were performed by Zhao et al [24] where thirty-two singlet and eightt riplet excited states with the corresponding oscillator strengths wered etermined by using aT D-DFT(PBE1PBE/LanL2DZ/CPCM) model. Based on am etal-ligand charge-transfer (LMCT) process of the azido ligand they confirmt he dissociative charactero ft he low-lying exited states.Q uantum chemistry parameters (for example, dipole moments, solvatione nergies, electrostatic potential, and partial charges) wereu sed in quantitative structure-activity relationship (QSAR)i nvestigations forn ovel cytotoxic Pt IV complexes by Varbanov et al…”
Section: Introductionmentioning
confidence: 99%
“…As imilar topic was also explored by Vicha et al [22] In contrastt op revious authors, they used the relativistic approach, that is, the two-component zeroth-order regular approximation (SO-ZORA) with the PBE0/TZP/COSMO computational level for successful determination of the NMR shielding constants.A nother interesting paper was recently published by Wilson et al [23] where, by combining experimental and computational tools, the oxidation of platinum(II) complexesw ith iodobenzene dichloride in DMF was studied, yieldingt he respectivep latinum(IV) analogues.T ime-dependent (TD)-DFT/ LANL2DZ/COSMO approachw as employed for the determination of the singlet excited states of both sets of Pt II and Pt IV complexes.T he calculations confirmed that the quenching of an excitation state (originally based on the LUMO in the Pt II complex) arises from the presence of metal-based dorbitals energetically positioned between the HOMO and the LUMO of the fluorophore ligand. Similar supporting calculations on diazido-platinum(IV) complexes were performed by Zhao et al [24] where thirty-two singlet and eightt riplet excited states with the corresponding oscillator strengths wered etermined by using aT D-DFT(PBE1PBE/LanL2DZ/CPCM) model. Based on am etal-ligand charge-transfer (LMCT) process of the azido ligand they confirmt he dissociative charactero ft he low-lying exited states.Q uantum chemistry parameters (for example, dipole moments, solvatione nergies, electrostatic potential, and partial charges) wereu sed in quantitative structure-activity relationship (QSAR)i nvestigations forn ovel cytotoxic Pt IV complexes by Varbanov et al…”
Section: Introductionmentioning
confidence: 99%
“…[3] A particularly potent photocytotoxic anticancer complex is trans,trans,trans-[Pt(N 3 ) 2 (OH) 2 (MA)(Py)] (1, MA = methylamine, Py = pyridine). [4] Herein we report the unprecedented oxidation of 5'-GMP by 1 upon irradiation with UVA and the identification of some unexpected reaction pathways involving singlet oxygen ( 1 O 2 ) and nitrene (Pt-N) intermediates. The source of the 1 O 2 was also investigated.…”
mentioning
confidence: 96%
“…Oxaliplatin was able to overcome some of the resistance associated with cisplatin. [8,9] Tetraplatinated porphyrins have long been used as supramolecular guests that interact with cationic, anionic, or neutral micelles [10] and have been studied as mimics of natural peroxidase. Hence, there is a growing need for new and effective drugs.…”
mentioning
confidence: 99%